Analisis Framing Pemberitaan Klitih dalam Berita Online di Daerah Istimewa Yogyakarta - Muhammad Nazhifuddin Fikri; Vani Dias Adiprabowo (Neolectura, 2023)
Media plays a crucial role in reporting cases of juvenile delinquency and street crimes. However, research indicates that news channels tend to provide disproportionate attention to cases of juvenile delinquency, indicating bias in news selection and the perspectives used. The phenomenon of 'klitih' in Yogyakarta serves as a unique example of juvenile delinquency, where the perpetrators harm victims without involving theft. This study is a qualitative research using Entman's framing analysis model to understand how the media constructs news. It is important for the media to provide accurate and non-exaggerated information. The results of the study show that the online news channels Harian Jogja and Tribunnews Jogja have similarities and differences in framing a street crime case. The similarity lies in their reliance on the police's point of view to confirm events at the crime scene. The difference is that Tribunnews Jogja provides a more comprehensive construction of the news, while Harian Jogja only presents some of the events that occurred at the crime scene